The Effects of Different Types of Music on Stress Levels (Global Journal of Human-Social Science, 2017)
A preliminary correlational research study was conducted to determine the relationship between different genres of music and stress among university students 94 Haigazian University students raging between the ages of 18 to 25 participated in the study 67 were females and 33 were males Two types of questionnaires were administered to them the music scale and the Perceived Stress Scale PSS Unlike mainstream studies the findings of this study conveyed that there is hardly any significant difference between stress and the frequency of listening to classical music Moreover the study indicated that there is no significant correlation between stress and the frequency of listening to other types of music such as Jazz Blues and Rock However the t-test sample revealed that there is a significant difference between the means of male and female on the dependent variable which is the stress This research is based on a random selection of Haigazian University HU students and ought to be extended to include other universities operating in Lebanon
Keywords: types of music; stress; classical music; males; females